2013
DOI: 10.5539/jsd.v6n4p118
|View full text |Cite
|
Sign up to set email alerts
|

Are There Effective Accounting Ways to Determining Accurate Accounting Tools and Methods to Reporting Emissions Reduction?

Abstract: Over the last century, many studies have used accounting methods and tools in focusing on environmental issues. This paper introduces readers to developments within the appropriate accounting tools designed to support firms and sectors reduction energy use as well as reducing greenhouse gases (GHGs) emissions. Current practice of traditional accounting (to date) has not covered environmental costs. Using Activity Based Costing could help firms to increase their understanding of sustainability and how to develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…Moreover, evidence provided by Wegener et al (2013) showed a positive relationship between ESG accounting and the age of firms. Meanwhile, other studies such as those of Sief (2014) and Almihoub et al (2013) found no relationship between firms’ age and their ESG accounting practice. Other authors such as García-Sánchez et al (2013) and Kansal et al (2014) demonstrated that firms’ age and industry affiliation is significantly related to the quantity and quality of environmental disclosures by firms.…”
Section: Literature Reviewmentioning
confidence: 84%
See 1 more Smart Citation
“…Moreover, evidence provided by Wegener et al (2013) showed a positive relationship between ESG accounting and the age of firms. Meanwhile, other studies such as those of Sief (2014) and Almihoub et al (2013) found no relationship between firms’ age and their ESG accounting practice. Other authors such as García-Sánchez et al (2013) and Kansal et al (2014) demonstrated that firms’ age and industry affiliation is significantly related to the quantity and quality of environmental disclosures by firms.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Age of firms: Previous studies establish that firms' age influences their ESG accounting practice. Wegener et al (2013), Almihoub et al (2013) and Sief (2014) found a relationship between firms' age and their ESG accounting practice. Consistent with these studies, the age of the firms was measured by the number of years they had been in existence.…”
Section: Econometric Approachmentioning
confidence: 99%
“…By measuring environmental innovation, Brunnermeier and Cohen (2003) statistically found an important relationship between pollution abatement costs and environmental innovation. On the other hand, some believe that environmental innovation may not necessarily reduce the marginal cost of pollution abatement (Almihoub et al, 2013;Bréchet & Jouvet, 2006).…”
Section: An Innovationmentioning
confidence: 99%
“…mitigation measures in the future (Baker, Chon, & Keisler, 2009;Bryan & Savitz, 2011). On a larger scale, this requires a variety of measuring and monitoring methodologies that can be applied to a range of sources to be used in different geographical regions and economic sectors (Almihoub, Mula, & Rahman, 2013;Lemon, Chave, Lampa, Fissel, & Buermans, 2004). There will be a need for information technology infrastructure and support programs to provide acceptable accuracy of results at a reasonable cost (Wexelblat & Srinivasan, 1999).…”
Section: Introductionmentioning
confidence: 99%